Endpoint Estimates for Commutators of Fractional Integrals Associated to Operators with Heat Kernel Bounds (Communications in Mathematical Research, 2020)
Let $L$ be the infinitesimal generator of an analytic semigroup on $L^2({\bf R}^n)$ with pointwise upper bounds on heat kernel, and denote by $L^{-\alpha/2}$ the fractional integrals of L. For a BMO function $b(x)$, we show a weak type $L{\rm log}L$ estimate of the commutators $[b,\ L^{-\alpha/2}](f)(x)=b(x)L^{-\alpha/2}(f)(x)-L^{-\alpha/2}(bf)(x)$. We give applications to large classes of differential operators such as the Schrödinger operators and second-order elliptic operators of divergence form.
Keywords: fractional integral; commutator; $L{\rm log}L$ estimate; semigroup; sharp maximal function